Technology-supported global education: A mixed method study - ÖZTÜRK, CEMİL (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2019)
The purpose of this study was to investigate the effects of using communication technologies in teaching of attainments related to global education in social studies course on students' academic success, knowledge retention and their opinions on teaching practice. The research was carried out on the 6th grade students in a secondary school in the province of Samsun. In the research, exploratory order model, one of the mixed method research designs, was used. There were 44 students in the experimental group and 41 students in the control group. Academic achievement test was used for data collection. The second phase of the study was designed as a case study and a semi-structured interview form was used to collect data. The interview form prepared for 10 students in the experimental group was applied. One-factor ANOVA was used for the repeated measures of the relationship between pretest, post-test and retention scores of the experimental and control groups to determine the retention of the program in learning. Descriptive analysis method was used in the analysis of qualitative data. At the end of the research, it was found that the technology supported teaching program applied to the experimental group was more effective in increasing students' academic achievement and learning retention compared to the teaching application in the control group which was not supported by communication technologies and where teacher-centered teaching -straight expression method- was used.
Keywords: Global education; Communication technologies; Social studies; STUDENTS ATTITUDES; MEDIA; ENGAGEMENT